The Design and Development of Android Based Mobile Application to Help Increasing Studentâs Emotional Quotient - Ubaidillah, Ahmad; Hakim, Abdul Barir (LPPM of STIMIK ESQ, 2018)
Intelligence Quotient (IQ) to a persons success is influential, but it turns out that Emotional Quotient (EQ) also plays an important role in ones success. This has been proved by several studies that are partly mentioned in this study. Although it has been proven, but support to help improve the EQ has not been found because this science is still relatively new and not a concrete science that can be measured with certainty. Therefore, the purpose of this study is to build an application that can help students in improving its EQ. This app is created by having two sessions, the first session is the EQ test and the calculation using the Fuzzy Mamdani method. For the second session is to issue the best advice by weighting on each suggestion to get suggestions based on EQ results. The software development method used in this research is RAD (Rapid Application Development) because it has the advantage of speed side to build a prototype. The result of this research is the application of expert system embodied in Android based mobile applications, Fuzzy logic used has advantages in detail, but in terms of category is still similar to boolean logic. And this application can perform EQ test and issue suggestions as planned.